Eight Steps to Developing A Simple Marketing Plan - Edward A. Evans; Fredy H. Ballen (EDIS, 2015)
Marketing is an essential component of any business, including agriculture. Despite the important role of marketing, many smallholding operators/growers are reluctant to create a marketing plan. This 5-page fact sheet provides a rationale for developing a marketing plan, a step-by-step process for creating one, and a marketing plan worksheet. Written by Edward A. Evans and Fredy H. Ballen, and published by the UF Department of Food and Resource Economics, August 2015. (Photo credit: iStock/Thinkstock)